THE INFLUENCE OF LEARNING INTEREST AND TEACHER'S TEACHING METHOD ON LEARNING ACHIEVEMENT OF GOVERNMENTAL ACCOUNTING - Puspita Ningrum, Olivia; Siswanto, Siswanto (Jurnal Pendidikan Akuntansi Indonesia, 2024)
This study aims to determine: (1) The Influence of Learning Interest on Learning Achievement of Governmental Accounting; (2) The Influence of the Teacher's Teaching Method on Learning Achievement of Governmental Accounting; (3) The Influence of Learning Interest and Teacher's Teaching Method on Learning Achievement of Governmental Accounting. This research type is ex-post facto with the subjects 107 student class XI AKL at SMK Negeri 1 Godean. Data collection techniques used were questionnaires, observation sheets, and documentation. The data analysis technique used is simple regression and multiple regression analysis. The results of the study show that: (1) There is a positive and significant influence Learning Interest on Learning Achievement of Governmental Accounting with a correlation coefficient (y) of 0.441; the coefficient of determination ( is 0.195. (2) There is a positive and significant influence Teacher's Teaching Method on Learning Achievement of Governmental Accounting with a correlation (y) of 0.421; the coefficient of determination ( is 0.178. (3) There is a positive and significant influence Learning Interest and Teacher's Teaching Method together on Learning Achievement of Governmental Accounting with a correlation coefficient () of 0.490; the coefficient of determination ( is 0.240.Keywords: Learning Achievement, Governmental Accounting, Learning Interest, Teacher's Teaching Method